Mutations institutionnelles et recompositions des territoires urbains en Afrique : une analyse à travers la problématique de l’accès à l’eau - Catherine Baron (Développement Durable et Territoires)
Access to water is one of the major challenges of urban policies implemented in developing countries. These policies aimed either to provide a global access in order to control urban spaces or to segment water supply to offer different services and features to comply with the diversity of actors. What is therefore the impact, in terms of spatial dimension, of different strategies followed by French speaking Sub-Saharan African cities ? In this paper, we combine approaches that explain conflicting actors' strategies with spatial analysis that explain the complexity of urban space organization. We outline three phases characterised by an original articulation among water governance modes and urban space organization. As a first step, we note that the trend towards dual urban organisation is reinforced by a segmented access to services. As a second step, we show how the measures advocated within the International Drinking Water Supply and Sanitation Decade of the eighties corresponded to the will to homogenise cities. As a third step, we assess the impact of models such as the private/public partnership model in the process of urban fragmentation which is currently the case of most French speaking Sub-Saharan cities.